Pemanfaatan Metode Kooperatif Tipe Teams Games Tournament Berbantuan Kartu Soal Warna (Kasona) untuk Meningkatkan Hasil Belajar Siswa - Mamuk Dhatun Nik Amah; Anna Mariyani; Muhammad Aunur Rofiq (Universitas Muhammadiyah Magelang, 2026)
This research was conducted to improve mathematics learning outcomes through the use This study aimed to enhance mathematics learning outcomes by employing the Teams Games Tournament (TGT) cooperative learning approach with coloured question cards (kasona) for fourth-grade elementary pupils. This research was undertaken due to the subpar learning results of students who attained mastery. The research methodology employed was Classroom Action Research, consisting of two cycles of implementation. The study was performed at SDN 1 Sumberagung Grade IV, including 20 students, comprising 11 males and 9 females as participants. Data were gathered via observation, assessments, interviews, and documentation. Data were analysed objectively to assess the enhancement of student learning outcomes and subjectively to evaluate the actions of teachers and students. The results indicated an enhancement in mathematics learning outcomes with multiplication content. During the pre-cycle, the mastery value rose from 15% to 75% in Cycle I. Moreover, in cycle II, the mastery rate attained 100%. The implementation of the TGT cooperative approach utilising coloured question cards enhances mathematical calculation abilities among fourth-grade primary students.